The Impact of Social Media Influencer on Attitude towards Local food and Behavioral Intention (A Study on Foreign Tourists Visiting Bali) - Thio, Sienny; Palumian, Yonathan (Politeknik Negeri Bandung, 2025)
The rapid growth of social media has completely changed the way people interact and communicate. This study examines the role of social media influencer in shaping foreign tourists' attitude toward local food and their behavioral intention, with the mediating role of foreign tourists' attitudes towards local food. Self-administered questionnaires surveys with 201 international tourist visiting Bali were collected between July and August 2023. The PLS-SEM using SmartPLS 4.0 was utilized to examine the proposed causal relationships among social media influencer, attitude towards local food, and behavioral intention. The results reveal a positive and significant influence of social media influencer and attitude towards local food on behavioral intention of foreign visitors. However, social media influencer was found to be insignificant in forming tourists' attitude. Attitude towards local food did not mediate the relationship of social media influencer and behavioral intention. This study provides insights into destination marketing efforts to attract more visitors and promote a destination by optimizing influencers of social media.